(untitled) (Research, Society and Development, 2021)
Erectile dysfunction (ED) is the inability to achieve or maintain an erection strong enough to allow intercourse. ED can be a total inability to achieve an erection, or an inconsistent and unpredictable ability to achieve a satisfactory erection, or even a tendency to maintain an erection for a short period of time. Before to start any type of treatment for erectile dysfunction, the cause should be screened and the criteria followed, thus avoiding surgery or any type of invasive procedure, before treating clinical issues and risk factors. Various treatments are available for erectile dysfunction Several treatment options for erectile dysfunction are currently available: electrotherapy, psychosexual counseling, the use of external vacuum devices, medications, intracavernous injection therapy, and the use of a prosthetic prosthesis. penis. Physiotherapeutic interventions provide non-invasive, painless, easy-to-perform, and low-cost treatment methods. The objective of this work is to describe erectile dysfunction as a health problem and its treatment through a physiotherapy approach. The methodology used consisted of a descriptive, relative and current study, through a scientific bibliographic survey. Based on research, physical therapy is considered effective in preventing and treating erectile dysfunction. However, more studies are needed to improve physical therapy and discover new techniques to use.